Advice through mice: individual and advisor-system differences in online recommendations. (12th May 2004) - Lynch, Patrick D.; Nunes, Paul F.; Kent, Robert J.
Internet advice and recommendations technologies provide innumerable ways for companies to help consumers make choices. However, basic questions about the acceptance and usefulness of online advice remain unanswered. A large web-based survey found differences in use of advice sources and topics, trust and confidence in human versus automated advice and preferences for advice speed and ease of use. Tactics and strategies for web vendor implementation of online advice systems are discussed.